2020
DOI: 10.1016/j.ijid.2020.07.070
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of viral clearance in the natural course of asymptomatic COVID-19: Comparison with symptomatic non-severe COVID-19

Abstract: Highlights Approximately 17% of the patients with COVID-19 exhibited no symptoms. The median time from diagnosis to negative conversion was about 2 weeks in the natural course of asymptomatic COVID-19. Time until negative conversion was shorter in asymptomatic COVID-19 than in symptomatic COVID-19. Rebound of cycle threshold values was not uncommon in follow-up RT-PCR assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
40
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 23 publications
5
40
1
1
Order By: Relevance
“…This could be attributed to our cohort’s nature as it consisted of young, healthy patients with a median (IQR) age of 30.0 (20–47), with a fewer number of patients had hypertension, diabetes mellitus, or other comorbidities. No gender effect on the viral shedding was seen in our cohort population, which is concordant with other studies’ findings, 7 , 29 , 36 including a study from the Republic of Korea by Noh et al in which 199 patients with COVID-19 with a mean age of 38.0 years, were found to have a mean duration of viral shedding of 24.5 days and was longer in symptomatic patients compared to asymptomatic ones (25.2 days versus 22.6 days, p < 0.01). 41 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This could be attributed to our cohort’s nature as it consisted of young, healthy patients with a median (IQR) age of 30.0 (20–47), with a fewer number of patients had hypertension, diabetes mellitus, or other comorbidities. No gender effect on the viral shedding was seen in our cohort population, which is concordant with other studies’ findings, 7 , 29 , 36 including a study from the Republic of Korea by Noh et al in which 199 patients with COVID-19 with a mean age of 38.0 years, were found to have a mean duration of viral shedding of 24.5 days and was longer in symptomatic patients compared to asymptomatic ones (25.2 days versus 22.6 days, p < 0.01). 41 …”
Section: Discussionsupporting
confidence: 93%
“…This could be attributed to our cohort's nature as it consisted of young, healthy patients with a median (IQR) age of 30.0 , with a fewer number of patients had hypertension, diabetes mellitus, or other comorbidities. No gender effect on the viral shedding was seen in our cohort population, which is concordant with other studies' findings, 7,29,36 including a study from the Republic of Korea by Noh et al in which 199 patients with COVID-19 with a mean age of 38.0 years, were found to have a mean duration of viral shedding of 24.5 days and was longer in symptomatic patients compared to asymptomatic ones (25.2 days versus 22.6 days, p < 0.01). 41 With the emergence of data indicating that although clinically recovered COVID-19 patients may continue to shed detectable-RNA in upper respiratory specimens for up to 3 months after illness onset, they are unlikely infectious to others; CDC released a new "symptoms-based" strategy for the completion and ending of quarantine or isolation for persons with COVID-19 in place of previously adopted "test-based" strategy.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…[ 15 16 ] One study compared disease course in asymptomatic and symptomatic patients of COVID-19 and found that around 17.2% of patients may be asymptomatic COVID-positive. [ 17 ] Authors found that asymptomatic patients may take lesser time to achieve negative conversion than the symptomatic population, and negative conversion within 20 days was also significantly higher in this group. [ 17 ] However, almost 50% of asymptomatic patients may not achieve negative conversion even after 2 weeks of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Authors found that asymptomatic patients may take lesser time to achieve negative conversion than the symptomatic population, and negative conversion within 20 days was also significantly higher in this group. [ 17 ] However, almost 50% of asymptomatic patients may not achieve negative conversion even after 2 weeks of diagnosis. Reports from China also have shown that almost 9.6% of residents in Wuhan who were never symptomatic, exhibited positive serology tests for COVID-19, indicating that they had an asymptomatic infection.…”
Section: Discussionmentioning
confidence: 99%